Impaired pulmonary gas exchange efficiency, but normal pulmonary artery pressure increases, with hypoxia in men and women with a patent foramen ovale. Issue 9 (17th July 2020) - Duke, Joseph W.; Beasley, Kara M.; Speros, Julia P.; Elliott, Jonathan E.; Laurie, Steven S.; Goodman, Randall D.; Futral, Eben; Hawn, Jerold A.; Lovering, Andrew T.
Abstract : New Findings: What is the central question of this study? Do individuals with a patent foramen ovale (PFO + ) have a larger alveolar‐to‐arterial difference in P O 2 ( A - a D O 2 ) than those without (PFO − ) and/or an exaggerated increase in pulmonary artery systolic pressure (PASP) in response to hypoxia? What is the main finding and its importance? PFO + had a greater A - a D O 2 while breathing air, 16% and 14% O2, but not 12% or 10% O2 . PASP increased equally in hypoxia between PFO + and PFO − . These data suggest that PFO + may not have an exaggerated acute increase in PASP in response to hypoxia. Abstract: Patent foramen ovale (PFO) is present in 30–40% of the population and is a potential source of right‐to‐left shunt. Accordingly, those with a PFO (PFO + ) may have a larger alveolar‐to‐arterial difference in P O 2 ( A - a D O 2 ) than those without (PFO − ) in normoxia and with mild hypoxia. Likewise, PFO is associated with high‐altitude pulmonary oedema, a condition known to have an exaggerated pulmonary pressure response to hypoxia. Thus, PFO + may also have exaggerated pulmonary pressure increases in response to hypoxia. Therefore, the purposes of the present study were to systematically determine whether or not: (1) the A - a D O 2 was greater in PFO + than in PFO − in normoxia and mild to severe hypoxia and (2) the increase in pulmonary artery systolic pressure (PASP) in response to hypoxia was greater in PFO + than in PFO − . We measured arterial blood gases and PASP via ultrasound in healthy PFO + ( n = 15) and PFO − ( n = 15) humans breathing air and 30 min after breathing four levels of hypoxia (16%, 14%, 12%, 10% O2, randomized and balanced order) at rest. The A - a D O 2 was significantly greater in PFO + compared to PFO − while breathing air (2.1 ± 0.7 vs . 0.4 ± 0.3 Torr), 16% O2 (1.8 ± 1.2 vs . 0.7 ± 0.8 Torr) and 14% O2 (2.3 ± 1.2 vs . 0.7 ± 0.6 Torr), but not 12% or 10% O2 . We found no effect of PFO on PASP at any level of hypoxia. We conclude that PFO influences pulmonary gas exchange efficiency with mild hypoxia, but not the acute increase in PASP in response to hypoxia. Abstract :